A randomized controlled trial to examine the impacts of disclosing personalized depression risk information on the outcomes of individuals who are at high risk of developing major depression: a research protocol - Wang, JianLi; MacQueen, Glenda; Patten, Scott; Manuel, Douglas; Lashewicz, Bonnie; Schmitz, Norbert (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Major depressive disorder is one of the most prevalent and disabling forms of mental illness in the general population. One public health strategy that may reduce the disease burden is early identification and prevention - identifying people who are at high risk and intervening to prevent symptoms from progressing into a major depressive episode (MDE). Multivariable risk predictive algorithms (MVRP) have been developed to estimate personalized risk (probability) of an MDE. The purpose of this trial is to answer the questions: (1) Does disclosure of personalized depression risk information promote high-risk individuals to take preventive actions? (2) Will disclosure of personalized depression risk information negatively affect the mental health of those at high risk? Methods We are recruiting 350 high-risk men and 350 high-risk women across the country. Individuals are eligible, if they: (1) are 18 years or older, (2) have not had a depressive episode in the past two months, (3) are at high risk of MDE based on the MVRPs (predicted risk of 6.5% + for men and of 11.2% + for women), (4) can communicate in either English or French, and (5) agree to be contacted for follow-up interviews. The MVRPs were developed and validated using longitudinal data from over 10,000 Canadians across the country. Eligible participants are randomized into (1) the control group, and (2) the group receiving personalized depression risk information. The participants are assessed at baseline, 6 and 12 months regarding accuracy of risk perception, use of self-help strategies and changes in psychological distress and functioning. Qualitative interviews are conducted in sub-samples of the intervention groups to explore how the personalized information affects risk perception, self-help behaviors and mental health. Discussion MVRPs can be used for risk stratification and planning preventive actions. The personalized risk information produced by MVRPs may also empower users to actively engage in self-management. This trial will contribute to the knowledge base about the potential health benefits and psychological harms associated with the provision of personalized depression risk information that will inform future implementation and patient-physician communication in the clinical settings. Trial registration NCT02943876 . Date of trial registration: October 21st, 2016.